KANDUNGAN LOGAM BERAT Fe, Cu, Zn, Pb, Co, Br PADA AIR LINDI DI TIGA LOKASI TEMPAT PEMBUANGAN AKHIR (TPA) DADAPREJO, KOTA BATU, DAU DAN SUPIT URANG, KABUPATEN MALANG - Hidayati Karamina; Ariani Trisna Murti; Tri Mujoko (Universitas Islam Kadiri, 2021)
Heavy metals where their presence in certain amounts is not harmful to living organisms, but if the amount exceeds the threshold it will be toxic. The character of heavy metals that are difficult to degrade, and easy to accumulate in the environment, so that some monitoring is needed to minimize the high content of heavy metals in leachate. The research was carried out in three locations TPA Dadaprejo Batu City, TPA Dau and TPA Supit Urang, Malang Regency, East Java. This research lasted for five months starting from May to September 2020. The materials used in this study were leachate water and leachate contaminated soil at the Dau Final Disposal Site, Dadaprejo, Supit Urang. The equipment used for this study were 600 ml bottles, filters, labels, plastic bags, scales, hoes, digital cameras and stationery. This research was conducted using sampling. The number of treatments consisted of 3 treatments which were repeated 3 times with the total amount of leachate being 9 samples. Leachate Sampling: There are 3 plots of leachate ponds at each location. Each pool plot was taken as much as 500 ml of leachate sample. Then obtained 3 samples from 3 plots, then samples of leachate from each plot were composited so that 1 sample was obtained representing each TPA. This leachate sample uses a grab sample technique where the wastewater is only temporary. To test the heavy metal content in leachate, it was identified by means of AAS (Athomyc Absorption Spectophotometer) which was carried out at the soil chemistry laboratory, Faculty of Agriculture, Universitas Brawijaya. The observation parameters The observed parameters were heavy metal content in leachate samples of heavy metals Iron (Fe), Copper (Cu), Zinc (Zn), Lead (Pb), Cobalt (Co), Boron (Br). The results showed the presence of heavy metals from leachate, namely, heavy metals iron (Fe), copper (Cu), zinc (Zn), lead (Pb), cobalt (Co), boron (B), cadmium (Cd), mercury ( Hg) which has a concentration value exceeding the quality standard threshold in accordance with the FAO, 2007 recommendation and Government Regulation Number. 82 of 2001.